Plasma electrolytic oxidation of Ti-6Al-4V alloy and its influence on the machinability during micro-milling. (January 2021) - Hu, Yizhong; Meng, Jianbing; Luan, Xiaosheng; Dong, Xiaojuan; Zhou, Haian; Qu, Linghui; Zhang, Hongwei; Wei, Xiuting
Graphical abstract: Highlights: Presentation of a new approach about plasma electrolytic oxidation assisted micro milling. Comparison of micro-milling characterization in conventional and PEO operations. Significant reduction in cutting force and surface roughness of PEOAM. Abstract: With the aim to modify the micro-milling behaviors of Ti6Al4V alloy for engineering application, a novel processing method of plasma electrolytic oxidation assisted micro-milling (PEOAM) was proposed in this paper. Ti6Al4V alloy was treated by plasma electrolytic oxidation (PEO) with an electrolyte mainly containing KH2 PO4 and Ca(CH3 COO)2, so that a low-strength oxide film that could be easily removed grew in-situ on the alloy surface. The oxide film was then subjected to micro-milling. The structure and composition of the oxide surface layer and sub-surface layer were characterized by scanning electron microscope and X-ray spectrometer. The cutting force of micro-milling applied to the oxide film was detected by dynamometer. Meanwhile, the milled surface roughness and top burrs were measured and analyzed by white light interferometer. The results indicated that PEO could promote the in-situ growth of 19 μm-thick loose and porous titanium oxide film on the surface of Ti6Al4V alloy. Compared with non-oxidation specimens, the microhardness and elastic modulus of the oxide surface layer were decreased by 34.5% and 47.1%, respectively. With the same micro-milling parameters, the cutting forces F x and F y were decreased by 51.4% and 71.4% respectively in down milling, and 36.2% and 88.4% in up milling. The surface roughness R a was decreased by 26.7%.